Linker-mediated oriented antibody immobilisation strategies for a more efficient immunosensor and diagnostic applications: A review - Shin Yi Gan; Gee Jun Tye; Ai Lan Chew; Woei Kean Ng; Ngit Shin Lai (Biosensors and Bioelectronics: X, 2023)
The conjugation of antibodies onto the solid surface in a well-oriented manner has a profound impact on the sensitivity and limit of detection of an immunoassay. The chosen method of immobilisation significantly influences the interaction between antibodies and antigens on the sensing surface. Optimal antigen capture capacity is achieved when the Fab fragments of the antibodies are properly oriented away from the surface. However, conventional approaches, such as physisorption and covalent conjugation, often lead to random immobilisation, which can ultimately result in the loss of antibody functional activity. To address these challenges, linker-mediated immunoassay (LMI) has been developed to precisely control the orientation of antibody. This review, thereby, presents the fundamental principles of oriented antibody immobilisation and highlights various target sites for controlled conjugation. Additionally, this review thoroughly discusses several linker-mediated immobilisation strategies based on different noncovalent interactions, including Fc binding proteins-mediated immobilisation, DNA-directed immobilisation, biotin-streptavidin-mediated immobilisation and Fc binding peptides-mediated immobilisation, accentuating their respective strengths and limitations. Hence, this review adds more to our understanding of the state-of-the-art of LMI technology, with a particular focus on the oriented immobilisation of full-length antibodies and its potential for future applications.